MENJAGA INTEGRITAS AKADEMIK DALAM TEOLOGI KRISTEN DAN PENDIDIKAN AGAMA KRISTEN MELALUI KEASLIAN TULISAN BERBASIS TURNITIN - Imanuel Taulangi; Destha Natasha Tandiassang; Jefri Sanda Badeng; Yenison Weya; Yudas Barihu (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
Academic integrity is a crucial aspect in education, particularly in Christian theology and Christian Religious Education, which emphasize the values ​​of honesty, responsibility, and truth. The development of digital technology facilitates easy access to information, but also raises challenges in the form of increased plagiarism and misuse of technology in scientific writing. This study aims to analyze the importance of maintaining academic integrity through the authenticity of Turnitin-based writing from the perspective of Christian theology and Christian Religious Education. The research method used is a literature study with a qualitative approach through the analysis of various journals, books, and relevant scientific sources. The results show that the use of Turnitin plays a significant role in helping maintain the originality of scientific work, building an honest academic culture, and increasing awareness of scientific writing ethics. In addition, the implementation of Christian values ​​through character education is a major factor in shaping students' academic responsibility in the digital era.